Human resources development as entrance in talent management - Odeesh, james Yohana; Abbas Al Mahmoud, Saad Fadel (Humanities Journal of University of Zakho, 2018)
The present research aims to identify the role of human resource development in talent management and through the field testing of data from sample of the administrative leaders at Duhok Polytechnic University. The researchers built a default model benefiting from the theoretical literature on the subject, which deals with the nature of correlation and impact between the research variables (Human resources development and talent management). Therefore, three main hypotheses have been formulated. The data collection through questionnaire, which was distributed to the administrative leaders at Duhok Polytechnic University, and it was analyzed by using a set of statistical methods in the SPSS program. The research found a number of conclusions, the most important of which is that the more attention Duhok Polytechnic University has to activities (career planning, training, performance evaluation and career change), it enhances the ability to manage talent, and that the change in the university is one of the most important factors contributing to attracting talent, talent development and talent retention. While the most important suggestions indicate that Duhok Polytechnic University should recognize and understand that its survival and success is related to its ownership of the management and care of talented human resources. So, the functions, activities and strategies of this department are considered as part of the daily work and life of the Duhok Polytechnic University.